al

posted by .

Multiply: -8/(7 )*(-7/4)

  • al -

    ((-8) / 7) * ((-7) / 4) = 2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    could you tell me three equivalent fractions for each: 2/3 8/16 4/10 3/4 Just multiply or divide by a common number. For example, 2/3 = 4/6 = 6/9 = 8/12 = 10/15 8/16 = 4/8 = 1/2 etc. Just multiply each fraction by 3 different numbers. …
  2. math

    how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 divide by 2 7x=16 x=16/7, which is 2 and 2/7 ok maybe you typed that question wrong?
  3. someone help

    my post is still on this page as algebra, could someone elaborate on what bobpursley tried to help me with. See your original post. I am guessing you are referring to your question 5)Simplify:(5x-4)^2 and your answer= 25x^2 - 16 (5x-4)^2 …
  4. Math

    I want to know did I work these problems right Multiply: ( - 6)² - 4² = 36 – 16 = 20 Multiply ( - 3) ( - 6 ) + ( 4 ) ( -2) = 18 + ( -8) = 18-8= 10 Multiply: ( - 3 ) ³ - ( - 8) ( -2) = (-3) times 3 = -9 (-8) times (-2) = 16 -9 …
  5. MATH

    1. To convert from kilometers (km) to meters (m), multiply by 1000. How many meters are there in 6.2 km?
  6. math

    what number makes the number sentence true?
  7. algebra

    Solve. x/9-1/7=26/63 STEP 1: The LCM is _________ To clear denominators, multiply each side of the equation by the LCM. _______/1 (x/9-1/7)=__________/1 multiply 26/63. STEP 2: Use the Distributive Property. _____/1 multiply x/9 - …
  8. Math, Please Help!

    Ned divided a given number by 3 and then added 2. If he should have multiplied the number by 3 and then subtracted 2, which of the following two steps can he do next to get the correct answer?
  9. Multiplying Polynomials

    Use the distributive property to write (each of) the following expression(s) as the sum of monomials. M. (t - 1)(t + 1)(t^2 + 1) I already know that I must multiply across, but I am a bit confused regarding the order to multiply in …
  10. Math

    A student is trying to solve the set of two equations given below: Equation A: x + z = 6 Equation B: 2x + 4z = 1 Which of the following is a possible step used in eliminating the z-term?

More Similar Questions